Hubungan antara Panjang Aksial Bola Mata dan Derajat Miopia dengan Tekanan Intraokular - Bella Aliviana (UNUSA Press, 2020)
Some studies reported that myopia especially high myopia has long axial length. This condition showed with higher intraocular pressure (IOP) and become one of the risk factor of primary open angle glaucoma. However, some other studies reported axial length and degree of myopia don’t have any correlation with intraocular pressure. This study aims to determine whether there is a relationship between the axial length of the eyeball and the degree of myopia with intraocular pressure at Sumatera Eye Center (SMEC), Samarinda. This study began on November to Desember 2019. This research method was analytic research with cross sectional design. The sample in this study was 91 eyes using a purposive sampling technique. Analyzes were performed with the Pearson Correlation test. The result showed the age of IOP increased at 31, 32, and 33 years old, respectively 1 eye. Pearson correlation test showed that IOP did not seem to have any correlation with the axial length, low myopia and high degree of myopia. But, IOP have correlation with moderate myopia (r=0,019).